2013
DOI: 10.1155/2013/749830
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Single-Pill Combination of Telmisartan 80 mg and Hydrochlorothiazide 25 mg in Patients with Cardiovascular Disease Risk Factors: A Prospective Subgroup Analysis of a Randomized, Double-Blind, and Controlled Trial

Abstract: Objective. Report of prespecified and post hoc subgroup analyses of a randomized, controlled trial comparing telmisartan 80 mg/hydrochlorothiazide 25 mg (T80/H25) combination therapy with T80 monotherapy, according to the presence of cardiovascular disease (CVD) risk factors. Methods. Hypertensive patients were randomized (2 : 1) to receive T80/H25 or T80 for 6 weeks, following a 1-week, low-dose, and run-in period. Systolic blood pressure (SBP) and diastolic BP reductions and BP goal achievement were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…dodatkową korzyścią stosowania telmisartanu i hydrochlorotiazydu jest rzadsze występowanie epizodów hipokaliemii niż podczas monoterapii hydrochlorotiazydem [15]. połączenie t/h wydaje się korzystne u pacjentów z nadciśnieniem tętniczym i dodatkowymi czynnikami ryzyka: otyłością, wysokim ryzykiem choroby wieńcowej, upośledzeniem czynności nerek [16][17][18]. podsuMoWAnIE telmisartan może być stosowany zarówno u pacjentów z niepowikłanym nadciśnieniem tętniczym, jak i u chorych z wysokim ryzykiem sercowo-naczyniowym, z nadciśnieniem tętniczym i uszkodzeniami narządowymi, ze współistniejącą chorobą nerek, z cukrzycą, z jawną chorobą miażdżycową, w tym tętnic obwodowych i po przebytym udarze mózgu.…”
Section: Słowa Kluczoweunclassified
“…dodatkową korzyścią stosowania telmisartanu i hydrochlorotiazydu jest rzadsze występowanie epizodów hipokaliemii niż podczas monoterapii hydrochlorotiazydem [15]. połączenie t/h wydaje się korzystne u pacjentów z nadciśnieniem tętniczym i dodatkowymi czynnikami ryzyka: otyłością, wysokim ryzykiem choroby wieńcowej, upośledzeniem czynności nerek [16][17][18]. podsuMoWAnIE telmisartan może być stosowany zarówno u pacjentów z niepowikłanym nadciśnieniem tętniczym, jak i u chorych z wysokim ryzykiem sercowo-naczyniowym, z nadciśnieniem tętniczym i uszkodzeniami narządowymi, ze współistniejącą chorobą nerek, z cukrzycą, z jawną chorobą miażdżycową, w tym tętnic obwodowych i po przebytym udarze mózgu.…”
Section: Słowa Kluczoweunclassified
“…Furthermore, a retrospective analysis showed that in black patients with hypertension and hypertensive patients with concomitant type 2 diabetes mellitus or moderate or severe renal impairment, T80/H25 resulted in greater reductions in SBP and DBP than telmisartan monotherapy, irrespective of baseline BP 27. A prespecified subgroup analysis of data from patients with stage 2 or 3 hypertension and CV disease risk factors, such as diabetes mellitus, low estimated glomerular filtration rate, high body mass index, and high coronary heart disease risk, reported that 6 weeks’ treatment with T80/H25 consistently provided greater BP reductions and increased BP goal-attainment rates compared with T80 monotherapy 56. A pooled analysis of data from seven studies showed that the efficacy and tolerability of the T/H SPC was similar between younger patients and patients older than 65 years (who may have added CV risk factors and are generally difficult to treat to goal) 57…”
Section: Which Combination For Which Patient?mentioning
confidence: 99%